MANAJEMEN STRATEGI PEMERINTAH DAERAH DALAM MENINGKATKAN INVESTASI PADA CENTRAL BUSINESS DISTRICT DI KABUPATEN KEDIRI - Wahyu Setyaningrum (Universitas Kadiri, 2019)
District/ city regional governments need to seek equal investment and income with other District/ City regions to avoid disparity/ inequality. This study uses strategic management theory and good governance. The research method in this text uses qualitative methods. The Government of Kediri Regency develops its territory to be used as a place of investment by building Gumul Lima Junction Kediri Regency. This effort was carried out with the 2012 KPM (Investment Office) work program. In the work program there was management at KPM in the form of planning, organizing, actuating and controlling. KPM implements strategy management, one of the strategy management tools through SWOT analysis (Strengths, Weakness, Opportunity, and Threats). So far, investors in SLG are still one investor, namely PT. Gumul Paradise Island. This is because it is difficult to get investors because it competes with Kediri City which is more strategically located. KPM in implementing strategic management uses SWOT analysis. Analysis is done by knowing the successes, failures, inhibiting factors, and supporting factors of the organization in carrying out its duties. After that, KPM gets a solution to the problems faced and can carry out the planning and development of work programs to face the challenges ahead. Establishing an atmosphere that is conducive to investing, investors need good and easy services in investing. This research was carried out in 2012, an interesting theme for further research on the development of investment in Kediri Regency.